Critical qualitative research in social education - White, Cameron (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
Critical qualitative research and social education are vital for the world of the 21st century. The onslaught of neoliberalism, corporatization, standardization, testing, and the continuing attack on public schools and educators necessitate critical approaches to teaching and learning along with critical qualitative research in social education. Ongoing issues with equity and social justice tied to race, ethnicity, class, orientation, age, and ability linking to schooling, education, teaching and learning must be addressed. The struggle between unbridled capitalism and democracy warrant these investigations in the 21st century, hopefully leading to advocacy and activism.This book explores critical qualitative research in social education, focusing on power, privilege, and social justice. It covers various topics, including the role of relationships, collaborative autoethnography, critical historical thinking, and transforming social studies classrooms. The chapters address issues like special education, deficit thinking, literacy skills, and international education, offering diverse perspectives and methodologies to empower educators and students.
Keywords: Social sciences -- Study and teaching -- Research.; Critical pedagogy.; Social justice -- Study and teaching.; Qualitative research.; Juvenile Nonfiction -- Social Science -- Sociology.; Social research and statistics.; Educational: Social sciences, social studies.; elektronické knihy; electronic books